MEANING OF ADJUSTMENT FOR WIFE WITH HUSBAND'S HAVE POLYGAMY - Anggraini, Hetty (Universitas Muhammadiyah Metro, 2015)
Abstract: This study aims to discover the meaning of adjustments for the wife whose husband's polygamy. Subjects in this study were 3 people who were selected based techniques purposivitas with the characteristics of the subject, the woman who was the first wife of a polygamous husband, aged between 40-70 years, have children, have their own income, and age polygamous marriage a minimum of 3 years. The data in this study were collected through participant observation and in-depth interviews. To assess the validity of the data used triangulation method. This research is a qualitative approach to multi-case study. The results of this study indicate that the meaning of adjustment for wives whose husbands are polygamous through life with not much demand, thanks to the existing favors. Life lived at this time is the road to self-closeness to the Creator and the path of devotion to Allah Subhannahu Wa Ta'ala. Meaning of adjustments for the wife whose husband polygamous sourced from creative values, experiential values , and attitudinal values.Keywords: polygamy, meaning, adjustments, marriage